Efecto del cuy macho introducido en las características, fenotípicas, morfométricas y productivas de la camada. - Dávila Collaguazo, Jennifer Nicole (2023)
In the present investigation, the effect of the introduced male guinea pig on the phenotypic, morphometric and productive characteristics of the litter was analyzed. Therefore, as a specific objective, the morphometric characteristics are defined as the basis for the selection of reproducers, this is advanced from the use of the methodology given a quantitative approach since it allows working with quantities, which, added to a descriptive type of investigation, will be taught. As the characteristics of the male help the new pups, through observation techniques for a period of 60 days using field cards, the data obtained from the young rabbits were recorded to know the improvement of each one of these, for the investigation There were 18 individuals, 3 males and 15 females, which were divided into three cages taking into account the place of origin of the male guinea pig, each cage having 5 females and 1 male. As a main conclusion, it is prolonged that, if there is an effect of the male guinea pig on the litter, being that of cage 1, the one that obtained the best results according to the imposed variables such as weight, length and width of the head, thoracic perimeter and body size.